2019
DOI: 10.3390/met9050564
|View full text |Cite
|
Sign up to set email alerts
|

GMAW Cold Wire Technology for Adjusting the Ferrite–Austenite Ratio of Wire and Arc Additive Manufactured Duplex Stainless Steel Components

Abstract: The use of commercially available filler metals for wire and arc additive manufacturing (WAAM) of duplex stainless steel components results in a microstructure with a very low ferrite content. The ferrite–austenite ratio in the duplex stainless steel weld metal depends on both the cooling rate and particularly on the chemical composition. However, the research and testing of special filler metals for additive deposition welding using wire and arc processes is time-consuming and expensive. This paper describes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 14 publications
1
27
0
Order By: Relevance
“…It was reported [26] that the ferrite content in subsequently deposited layers is reduced along with hardness compared to the support plate. Stützer et al [27] used a new approach for estimation of ferrite (α)/austenite (γ) balance with different wires and CMT technology and achieved a balance of 50%/50% of austenite and ferrite with good mechanical and corrosion properties.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported [26] that the ferrite content in subsequently deposited layers is reduced along with hardness compared to the support plate. Stützer et al [27] used a new approach for estimation of ferrite (α)/austenite (γ) balance with different wires and CMT technology and achieved a balance of 50%/50% of austenite and ferrite with good mechanical and corrosion properties.…”
Section: Introductionmentioning
confidence: 99%
“…Their microstructure features and mechanical properties are quite different after WAAM. Stützer et al found that mixing different filler metals can reduce the nickel equivalent and increase the ferrite content in GMAW duplex stainless steel specimens [89]. Moreover, appropriate process parameters can help to achieve a high-quality WAAM structure.…”
Section: Addilanmentioning
confidence: 99%
“…Other factors also have specific effects on phase balance, including material composition [105] and heat treatments [91]. For instance, in the investigation of adjusting the ferrite-austenite ratio of WAAM duplex stainless steel components, Stützer et al [89] mixed two different filler metals to decrease the nickel equivalent, thus increased the ferrite content in the specimens. The sample fabricated with 100% of the filler metal G 22 9 3 (see Figure 7a) contains large austenitic side plates.…”
Section: Microstructurementioning
confidence: 99%
See 2 more Smart Citations